Freestanding MOF microsheets with defined size and geometry using superhydrophobic-superhydrophilic arrays - Tsotsalas, Manuel; Maheshwari, Himanshu; Schmitt, Sophia; Heißler, Stefan; Feng, Wenqian; Levkin, Pavel (Advanced materials interfaces, 2016)
Superhydrophobic-Superhydrophilic arrays are used to control the size and shape of freestanding metal-organic framework (MOF) microsheets. The MOF sheets are prepared at the liquid-liquid interface of an aqueous copper acetate solution confined in microdroplets and a 1-octanol solution of trimesic acid. The resulting MOF microsheets can be suspended in solution or transferred to other substrates.
Gesehen am 29.05.2020